The book of Nero 7 : CD and DVD burning made easy - Wang, Wally (No Starch Press, 2006)
Ahead Software's Nero program is the most popular CD and DVD burning software in the world. While it seems like it should be easy to burn CD's and DVDs, doing so can be much more complicated than it appears, and many users reach high frustration levels after burning multiple coasters that don't work. This simple, task-oriented, step-by-step book covers the entire Nero program suite, including audio CD burning, data backup, managing photos, DVD video burning, designing CD/DVD labels, editing sound, creating a virtual drive and CD/DVD data disk, and playing audio and video. This updated revision.